ABILITY OF NET INCOME IN PREDICTING DIVIDEND YIELD: OPERATING CASH FLOW AS A MODERATING VARIABLE - Puspitaningtyas, Zarah (Archives of Business Research, 2018)
The purpose of this study is to determine the ability of net income in predicting dividend yield with operating cash flow as a moderating variable on manufacturing companies of the consumer goods industry sector listed in the Indonesia Stock Exchange on the period 2012-2016. The sample is selected by using purposive sampling technique. The data analyzed by using moderated regression analysis. The result of analysis shows that, at the 0.05 level of significance, operating cash flow significantly influences the dividend yield, while net income does not affect the dividend yield. However, operating cash flow is able to moderate significantly the effect of net income on dividend yield. These results indicate that net income is unable to signal investors to predict dividend yields. However, net income will be a significant explanation of the dividend yield when operating cash flow acts as a moderating variable.